1992
DOI: 10.2307/3578422
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Related Ophthalmological Changes and Aging among Hiroshima and Nagasaki A-Bomb Survivors: A Reanalysis

Abstract: The relationship of ionizing radiation to the age-related ophthalmological findings of the 1978-1980 ophthalmological examination of A-bomb survivors of Hiroshima and Nagasaki has been reanalyzed using DS86 eye organ dose estimates. The main purpose of this reevaluation was to determine whether age and radiation exposure, as measured using the recently revised dosimetry information (DS86), have an additive, synergistic, or antagonistic effect. The data in this study are limited to axial opacities and posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…Several different studies reported that exposure at an early age confers more risk per unit dose than exposure at a later age (26,30,32,41), although other human data have not provided support for this (33). Most data sets, however, have had only a limited age range, so arriving at a broad-based answer is difficult.…”
Section: Status Of Risk Assessmentmentioning
confidence: 89%
“…Several different studies reported that exposure at an early age confers more risk per unit dose than exposure at a later age (26,30,32,41), although other human data have not provided support for this (33). Most data sets, however, have had only a limited age range, so arriving at a broad-based answer is difficult.…”
Section: Status Of Risk Assessmentmentioning
confidence: 89%
“…All the opacities detected at ophthalmological examinations were minor. Nuclear opacities were the most common finding [8 (14%) subjects (95% CI 6-26), including nuclear colour changes observed in 6 (11%) subjects (95% CI [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Cortical opacities (grade 1-2 changes) were found in 4 (7%) cases (95% CI 2-17%), with 9 (17%) additional subjects (95% CI 7-28) showing cortical traces.…”
Section: Resultsmentioning
confidence: 99%
“…Re-analyses of atomic bomb survivor data have demonstrated that the findings are compatible both with threshold (about 1.5 Sv) and linear models (10)(11)(12)(13). In one study, children whose lens was exposed to 1 Gy during radiotherapy had a 50% increased risk of developing a posterior subcapsular opacity and a 35% higher risk for cortical lens opacities, compared with unexposed controls (16).…”
mentioning
confidence: 87%
See 2 more Smart Citations